2020
DOI: 10.2903/j.efsa.2020.6174
|View full text |Cite
|
Sign up to set email alerts
|

Update of the list of QPS‐recommended biological agents intentionally added to food or feed as notified to EFSA 12: suitability of taxonomic units notified to EFSA until March 2020

Abstract: The qualified presumption of safety (QPS) was developed to provide a generic safety evaluation for biological agents to support EFSA's Scientific Panels. It is based on an assessment of the taxonomic identity, the body of knowledge, safety concerns and antimicrobial resistance. Safety concerns identified for a taxonomic unit (TU) are where possible to be confirmed at strain or product level, reflected by ‘qualifications’. No new information was found that would change the previously recommended QPS TUs of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 133 publications
1
63
0
Order By: Relevance
“…Saccharomycetales species involved in bread-related fermentation are most often the only species found using culture-based methods [ 30 ]. The prospective analysis of a wide range of cereal matrices from Spain allowed us to identify yeast species with the status of Qualified Presumption of Safety (QPS), which are considered as food-grade microorganisms [ 107 , 108 , 109 ]. Of the 513 microbial colonies originally recovered from different matrices, 433 isolates belonging to 9-QPS yeast species were selected for further studies ( Table S1 ) and 81 were discarded (~16%) ( Table S4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Saccharomycetales species involved in bread-related fermentation are most often the only species found using culture-based methods [ 30 ]. The prospective analysis of a wide range of cereal matrices from Spain allowed us to identify yeast species with the status of Qualified Presumption of Safety (QPS), which are considered as food-grade microorganisms [ 107 , 108 , 109 ]. Of the 513 microbial colonies originally recovered from different matrices, 433 isolates belonging to 9-QPS yeast species were selected for further studies ( Table S1 ) and 81 were discarded (~16%) ( Table S4 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the European Food Safety Authority (EFSA) evaluated a number of traditional species of probiotics as safe for application in food by the Qualified Presumption of Safety (QPS) [ 121 ]. From October 2019 to March 2020, EFSA found that only 6 microorganisms met the standard from 39 notifications [ 122 ].…”
Section: Probiotic Applicationsmentioning
confidence: 99%
“…Several Lactobacillus species are shown to have probiotic properties [ 23 , 26 ]. Further, many Lactobacillus probiotics have the notification “generally regarded as safe” (GRAS) issued by the United States Food and Drug Administration (FDA) [ 23 , 26 ] and also fall under “qualified presumption of safety” (QPS) in the European Union (EU) [ 27 ]. Lactobacilli are abundant in the GIT of pigs [ 26 ], thus urging investigations of their potential as pig-specific probiotics.…”
Section: Introductionmentioning
confidence: 99%